2010
DOI: 10.1128/iai.00739-10
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-Related Variation in Susceptibility to Complement Deposition and Opsonophagocytosis among Clinical Isolates of Streptococcus pneumoniae

Abstract: The polysaccharide capsule is a major virulence factor of Streptococcus pneumoniae; it affects complement resistance and shields the bacterium from phagocytes. Certain capsular serotypes appear to be better able to cause invasive disease than others. Serotypes 1 and 5 are common causes of invasive disease but are rarely isolated from healthy carriers, whereas serotypes 6B and 23F are more frequently isolated from carriage than invasive disease. We have recently shown that serotypes 6B and 19F differ in resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 60 publications
2
34
0
2
Order By: Relevance
“…However, the exceedingly high estimation of the invasive disease potential of serotype 4 was based on a total of six cases, four of which had the same MLST, 205 (4). Serotype 4 invasive isolates in the previous study (three isolates, two of which MLST 205) were more resistant to complement deposition than serotypes 14 and 23F, whereas the serotype 4 reference strain used in the standard opsonophagocytic assay was significantly more sensitive to complement than the clinical isolates (31). In the present study the serotype 4 TIGR4 strain was inferior to all other capsule-switched mutants.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…However, the exceedingly high estimation of the invasive disease potential of serotype 4 was based on a total of six cases, four of which had the same MLST, 205 (4). Serotype 4 invasive isolates in the previous study (three isolates, two of which MLST 205) were more resistant to complement deposition than serotypes 14 and 23F, whereas the serotype 4 reference strain used in the standard opsonophagocytic assay was significantly more sensitive to complement than the clinical isolates (31). In the present study the serotype 4 TIGR4 strain was inferior to all other capsule-switched mutants.…”
Section: Discussionmentioning
confidence: 42%
“…We have previously found that pneumococcal isolates of certain serotypes, such as 1 and 5, associated with invasive disease were particularly resistant to complement deposition and opsonophagocytic killing, while serotypes such as 6B and 23F, associated with carriage, were more sensitive to deposition of C3 and opsonophagocytosis (30,31). We found significant variation in the magnitude of complement deposition between isolates expressing the same capsular serotype, suggesting a role of serotype-independent factors in the outcome of this particular interaction.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Published studies report how the characteristic of the capsule of S. pneumoniae strains can affect the site and quantity of complement deposition (19,40,42), and this could account for the different responses to in vitro killing obtained here. Furthermore, a variable concentration of capsular polysaccharide-specific antibodies is required to obtain similar OPKA levels, suggesting that these antibodies could also have different functional properties (24,25). In light of this, we cannot exclude the possibility that the different OPKA results observed for the three pilus-positive strains could be due to different functionalities of the antibodies directed against the three variants constituting the fusion protein.…”
Section: Discussionmentioning
confidence: 65%